Optimization of Process Parameters for a Vertical Shaft Impact Crusher through the CFD-DEM Method - Sun, Ke; Zhao, Limei; Long, Qitao (Manufacturing Technology Journal, 2024)
In this study, the process parameters of a vertical shaft impact (VSI) crusher are optimized. Different feed size distributions, material physical properties, and product size distribution requirements are considered to determine the optimal material particle bond cleavage ratio. First, a numerical model is developed to simulate the crushing effect by adopting a CFD-DEM method. Then, the relationship between the crushing effect and the rotor speed, feed size distribution, and feed rate is revealed by analyzing the bond cleavage ratio of smaller-size distribution feed crushing to the specified particle size. The optimized working parameters of the crusher are determined under different feed size distributions. The results show that the feed size distribution of 8 mm, 20 mm, and 40 mm account for 20%, 30%, and 50% of the feed, respectively. Based on the results, it is implied that a feed rate of 120 t/h and a rotor rotational speed of 1800 r/min can be selected for crushing production. When the feed size distribution varies, this method can also be used to select a suitable feed rate and the rotor speed for crushing production. Overall, this study guides for optimizing the working parameters and improving the crushing efficiency.
Keywords: VSI crusher; Working parameters; Optimization; CFD-DEM